FINDING IDENTITY IN A SMALL ISLET COMMUNITY: A study of raison d’être of a micro-society in 2019 Denmark - Ahlefeldt-Laurvig-Bille,Marie-Sophie Elisabeth (2020)
This thesis explores how the production of identity happens on a small islet community in Denmark’s South Funen Archipelagos. Furthermore, it investigates in what way the residents make use of this islet identity, through memory, imaginings and collective action, in order to provide ground for raison d’être. Through a qualitative approach, a three months fieldwork was conducted in the summer of 2019. Analysis revealed that the residents make use of the islet’s limitations to create a state of exception, where that which is not possible is used actively to argue for their survival. Concluding that it is through substantial collective work of making sure that things are in order, that the state of exception is realised as a matter of forgetting about time. The state of exception is thus providing Birkholm with raison d’être in 21st century Denmark.
Keywords: Social Anthropology; Islet Community; Identity; Raison d’être; State of Exception